102k views
1 vote
Some help?I don't know how to solve it​

Some help?I don't know how to solve it​-example-1

1 Answer

4 votes
This is an inequality. Change the < sign to an = sign and solve the equation.

You can simplify 2log base2 (x) by moving the 2 inside the logarithm.

Log base 2 (6-x) = log2 (x^2)

For the equation to be equal the argument of the logarithm on both sides of the equation must also be equal.

6-x = x^2

Solve for X.

X = 2, -3

I hope that helps.
User Quietmint
by
5.2k points